2016
DOI: 10.1177/1367006915600800
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory role of inhibition during language switching: Evidence from evoked and induced oscillatory activity

Abstract: Aims: The present study adopted the electroencephalogram (EEG) technique to investigate whether inhibition advantage could modulate different language switches, regardless of the time spent on second language learning. Design: The inhibitory control (IC) ability of 80 low-proficient Chinese (L1)-English (L2) bilinguals was assessed by the Simon task. Half of these bilinguals were then subdivided into 20 high- and 20 low-IC participants to perform switching between L1 and L2 (L1–L2 switching), and the other hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Moreover, other studies have shown an overlap in the mechanisms between language control and domain-general control (e.g., Declerck, Grainger, Koch & Philipp, 2017; Prior & Gollan, 2013). These findings suggest that variances in inhibitory control ability between individuals play an important role in modulating language switch costs and that they should be considered within the ICM framework (Liu et al, 2014; Liu et al, 2015; Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Moreover, other studies have shown an overlap in the mechanisms between language control and domain-general control (e.g., Declerck, Grainger, Koch & Philipp, 2017; Prior & Gollan, 2013). These findings suggest that variances in inhibitory control ability between individuals play an important role in modulating language switch costs and that they should be considered within the ICM framework (Liu et al, 2014; Liu et al, 2015; Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…More recently, researchers have posited that the individual capacity of cognitive control also plays an analogous role in modulating language switch costs (Liu et al, 2015(Liu et al, , 2016. Liu et al (2015) found that the language switch costs of non-proficient bilinguals with high IC were symmetrical while that of nonproficient bilinguals with low IC were not.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, within L1, competing lexical representations may have been activated because they were related to the target word or were evoked by the visual stimulus, and the activation level of the target L1 lexical representation must exceed that of its L1 competitors to ensure production of the correct lexical item. Although it may be possible for domain-general control processes to be recruited during the process of lexical selection (e.g., Liu, Rossi, Zhou & Chen, 2014; Liu, Liang, Zhang, Lu & Chen, 2015), language-specific mechanisms may be more likely to regulate activation levels of lexical representations within a language.…”
mentioning
confidence: 99%